(untitled) (Revista Española de Derecho Internacional, 2009)
Applicable Law to the merits in international commercial arbitration performs a constructive and an interpretative function related to legal treatment of contracts and obligations between the parties. However, this article defends the exclusion of a traditional restrictive function, that is why the peremptory norms of the lex causae will only be applied as mandatory rules as those from any third State. The reasons for the application of mandatory or public policy rules in international commercial arbitration can be founded in three circumstances: close connection of the situation, predictability and international recognition of public policy. This article also contents a critical approach to the lex mercatoria in the wide sense, beyond the commercial practices. It analyses the inconvenient identification of UNIDROIT Principles as the lex mercatoria and the need for accepting their application as far as they can be considered to reflect generally accepted principles and rules. In recent times, the question of determining applicable Law on the merits in international commercial arbitration has got rid of characteristic solutions of private international law applied by national judges. However, this increasing independence is not necessarily appropriate to the legitimate wish of autonomy and transnational character of arbitration and it has not a positive effect on security and predictability in international trade law, either. Arbitration in XXIth century, a reinforced autonomy principle, legal security and predictability, they all need a determination of the law applicable to the merits founded on the freedom of choice of law by the parties, but also on the responsibility of arbitrators in supporting their own choice about legal sources even in cases of no choice by the parties.